Effect of Surface Polishing on Mercury Release from Dental Amalgam After Treatment 16% Carbamide Peroxide Gel - M. Azarsina; Sh. Kasraei; T. Masoum; Z. Khamverdi (Tehran University of Medical Sciences, 2011)
Objectives: This study evaluated the effect of surface polishing on mercury release from dental amalgam after treatment with 16% carbamide peroxide gel. Materials and Methods: Ninety-six samples from two different amalgam brands were prepared in truncated cone-shaped PVC polymer molds with an external surface area of 195 mm². Half of the specimens were polished with green and red rubber, a brush and tin oxide paste at low speed. Samples were treated with 16% carbamide peroxide gel in tubes containing 3 mL of carbamide peroxide gel and 0.1 mL of distilled water for 14 and 28 hours. Subsequently, carbamide peroxide gel on the sample surfaces was rinsed away with 7.0 mL of distilled water until the volume of each tube increased to 10 mL. The mercury level of each solution was measured using the VAV-440 mercury analyzer system. Considering the surface area of each amalgam disc, mercury amounts were calculated in μg ⁄mm². Data were analyzed using two-way ANOVA. Results: There were significant differences between the mean levels of mercury release from polished vs. unpolished amalgam surfaces after treatment with 16% carbamide peroxide. Increasing the storage time from 14 to 28 hours did not result in significant changes in the amount of mercury release. There was no significant interaction effect between amalgam surface polish and storage time statistically. Conclusion: Polished amalgam restorations release less mercury after treatment with carbamide peroxide bleaching gel in comparison with unpolished amalgam restorations.